Altered Core Temperature and Salivary Melatonin in Athletes with a Cervical Spinal Cord Injury - Murphy, Conor J; Hartescu, Iuliana; Leicht, Christof A; Goosey-Tolfrey, Victoria L (International Journal of Sports Medicine, 2022)
Sleep disturbances are common in athletes with a cervical spinal cord injury (cSCI) and may be associated with circadian alterations. Therefore, the purpose of this study was to compare physiological circadian outputs between athletes with a cSCI and non-disabled controls (CON). Eight male wheelchair athletes with a cSCI and eight male CON (30±4 and 30±6 yrs, respectively) had their core body temperature (Tcore), skin temperature (Tskin), and salivary melatonin measured during a 24 h period. In the cSCI group, daytime Tcore was significantly lower (36.5 (0.2) vs 36.9 (0.3)°C; p=0.02) and time of the Tcore sleep minimum was significantly earlier (23:56±00:46 vs 02:39 ± 02:57; p=0.04). The athletes with a cSCI had significantly lower Tcore values during the beginning of the night compared with the CON group, but their Tcore increased at a greater rate, thereafter, indicated by a significant time/group interaction (p=0.04). Moreover, the cSCI group did not display a salivary melatonin response and exhibited significantly lower concentrations at 22:00 (p=0.01) and 07:00 (p=0.01) compared with the CON group. Under natural living conditions, athletes with a cSCI displayed circadian changes in the Tcore rhythm and nocturnal melatonin production.
Keywords: paralympic sport; disability; sleep; chronobiology; wheelchair rugby, wheelchair tennis